Highly efficient transformation of linear poly(phenylene ethynylene)s into zigzag-shaped π-conjugated microporous polymers through boron-mediated alkyne benzannulation. (21st February 2018) - Shoji, Yoshiaki; Hwang, Minsu; Sugiyama, Haruka; Ishiwari, Fumitaka; Takenouchi, Kumiko; Osuga, Ryota; Kondo, Junko N.; Fujikawa, Shigenori; Fukushima, Takanori
Abstract : Linear poly(phenylene ethynylene)s are directly converted into zigzag-shaped π-conjugated microporous polymers. Abstract : Porous polymers offer great advantages compared to other microporous materials in terms of solubility and processability. However, the design of porous polymers has suffered from the limited availability of suitable building blocks. Here we propose a conceptually new strategy for the design of porous polymers, which involves the transformation of a rigid linear polymer into a rigid zigzag polymer with a large free volume around the polymer backbone. This strategy relies on a boron-mediated alkyne benzannulation reaction, which was recently developed by our group. When the benzannulation reaction was applied to poly(phenylene ethynylene) (PPE) derivatives, a linear-to-zigzag structural transformation successfully occurred to give the corresponding π-conjugated polymers with a diarylphenanthrene unit in the main chain. As revealed by N2 adsorption experiments, while the parent PPEs were non-porous, the zigzag polymers in the solid state possessed porosity with a specific surface area of up to 366 m 2 g −1, where the surface area largely depended on the steric bulkiness of the substituents on the polymer. Considering the fact that a wide variety of PPE derivatives have so far been synthesized, the present strategy may open a new avenue for the development of functional porous polymers.